Strategi Meningkatkan Iman SEKAMI melalui Pemanfaatan Media Sosial Tik-tok di Stasi Kristus Raja Semesta Alam Suga-Suga - Sergius Lay; Kristiana Mendrofa; Venida Anastasya Limbong (Jurnal Magistra, 2025)
The title of this study is a strategy to increase the faith of SEKAMI through the use of tik-tok social media at Stasi Kristus Raja Semesta Alam Suga-Suga. The focus of the research stems from the researcher's concerns about the support of SEKAMI, which does not have a strategy or approach to address SEKAMI children on a case-by-case basis. The main problem identified is the lack of understanding of the development of the situation, hence the absence of a good strategy to exploit the situation, especially in terms of technology that displays different types of social media, including tik-tok. social media. The purpose of this research is to look at, which includes tik-tok social media, which is one of the methods that can be used to increase the trust of SEKAMİ. The research method used is qualitative research. The selection of research sites and subjects was done through random sampling and random sampling. Miles and Huberman model was used to analyze the data. The analysis was performed in three stages: data reduction, data presentation, and data control. The framework is to explain's strategy of using tik-tok social media to SEKAMI trust. Based on research, the research results illustrate that SEKAMI facilitators will collaborate tik-tok social media with SEKAMI activities because they have found various strategies to utilize tik-tok social media as one of the tools that can be used in increasing SEKAMI's